Effects of semen sexing kits (HeiferplusTM and BullplusTM) supplemented to frozen-thawed bull semen on pregnancy rates, foetal sex ratios and selected reproductive parameters in cows - Türk, G; Yüksel, M; Sönmez, M; Gür, S; Özer Kaya, Ş; Demirci, E (My University, 2015)
It has been claimed that artificial insemination (AI) of cows with frozen-thawed semen treated with commercially produced kits, HeiferplusTM (HP, in favour of female gender) and BullplusTM (BP, in favour of male gender), increases the birth chance of calves with desired sex ratio by at least 20–25% and pregnancy rates by at least 5–20%. Hence, this study was conducted to investigate the efficacy of HP and BP kits as combined with AI on the pregnancy rates, foetal sex ratios and some reproductive parameters in cows. For this, a total of 200 cows (100 Holsteins and 100 Simmentals) from three to five years old were used. Fifty Holstein and 50 Simmental cows served as controls. The other half of Holstein and Simmental cows was artificially inseminated with frozen-thawed semen treated with HP and BP, respectively. Findings showed that the AI of cows with frozen-thawed semen treated with HP had no significant effect on the pregnancy rate [52.0% (26/50) in HP group; 56.0% (28/50) in control group], female calf ratio [52.0% (13/25) in HP group; 44.4% (12/27) in control group], embryonic death, abortion, stillbirth, twinning and gestation length as compared to the control group. Similarly, AI of cows with frozen-thawed semen treated with BP did not lead to any significant effect on the pregnancy rate [64.0% (32/50) in BP group; 58.0% (29/50) in control group], male calf ratio [53.1% (17/32) in BP group; 39.3% (11/28) in control group] and other reproductive parameters as compared to the control group. In conclusion, HP and BP treatments of semen used in the AI provided only slight, non-significant increases in female (7.6%) and male (13.8%) calf ratios, respectively.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Heiferplus Bullplus Foetal sex Pregnancy rate Cow